Identification of molecular network of gut-brain axis associated with neuroprotective effects of pparδ-ligand erucic acid in rotenone-induced parkinson's disease model in zebrafish - ALTURFAN, EBRU IŞIK (My University, 2022)
Disruption of the gut-brain axis in Parkinson's disease (PD) may lead to motor symptoms and PD pathogenesis. Recently, the neuroprotective potential of different PPARδ-agonists has been shown. We aimed to reveal the effects of erucic acid, peroxisome proliferator-activated receptors (PPARs)-ligand in rotenone-induced PD model in zebrafish, focusing on the gutbrain axis. Adult zebrafish were exposed to rotenone and erucic acid for 30 days. LC-MS/MS analysis was performed. Raw files were analyzed by Proteome Discoverer 2.4 software, peptide lists were searched against Danio rerio proteins. STRING database was used for protein annotations or interactions. Lipid peroxidation (LPO), nitric oxide (No), alkaline phosphatase, superoxide dismutase, glutathione S-transferase (GST), acetylcholinesterase, and the expressions of PD-related genes were determined. Immunohistochemical tyrosine hydroxylase (TH) staining was performed. LC-MS/MS analyses allowed identification of over 2000 proteins in each sample. 2502 and 2707 proteins overlapped for intestine and brain. 196 and 243 significantly dysregulated proteins in the brain and intestines were found in rotenone groups. Erucic acid treatment corrected the changes in the expression of proteins associated with cytoskeletal organization, transport, and localization and improved locomotor activity, expressions of TH, PD-related genes (lrrk2, park2, park7, pink1), and oxidant-damage in brain and intestines in the rotenone group as evidenced by decreased LPO, No, and increased GST. Our results showed benefical effects of erucic acid as a PPARδ-ligand in neurotoxin-induced PD model in zebrafish. We believe our study, will shed light on the mechanism of the effects of PPARδ agonists and ω9-fatty acids in the gut-brain axis of PD.
Keywords: Parkinson's disease; gut-brain axis; ω9-fatty acids; LC-MS/MS analyzes; zebrafish; rotenone